Dedekindove vsote in kvadratni reciprocitetni zakon - Renko Zver, Rebeka (Obzornik za matematiko in fiziko, 2012)
We introduce the Dedekind sums with a related reciprocity formula which leads us to derivation of the known quadratic reciprocity law.
Keywords: Dedekindove vsote; reciprocitetna formula; teorija števil